Dermatomyositis‐like disease in a Rottweiler. Issue 3 (5th May 2014) - Bresciani, Francesca; Zagnoli, Laura; Fracassi, Federico; Bianchi, Ezio; Cantile, Carlo; Abramo, Francesca; Pietra, Marco
<x xml:space="preserve">Abstract</x> Background Canine dermatomyositis is a hereditary disease described in collies and Shetland sheep dogs and their cross‐breeds. A similar disease, called dermatomyositis‐like disease, has been described occasionally in other breeds but never in the Rottweiler. Hypothesis/Objectives We report on the clinicopathological findings associated with dermatomyositis‐like disease in a Rottweiler. Animal A 7‐month‐old female Rottweiler was referred for dermatological abnormalities, regurgitation and weakness. Cutaneous abnormalities included alopecia, crusting and scaling on the inner surface of the pinnae, the tip of the tail, periorbital and perilabial skin. The dog also presented onychogryphosis and onychalgia. Methods Complete blood count, serum biochemistry panel, thoracic radiographs, electromyography, nerve‐conduction studies and skin and muscle biopsies were performed. Results Megaoesophagus, pneumonia, ischaemic dermatopathy and generalized myositis were documented. The final diagnosis was dermatomyositis‐like disease. Conclusions and clinical importance This is the first report of dermatomyositis‐like disease in a Rottweiler.